A luta dos trabalhadores rurais pela terra e a organização Política em face dos grandes empreendimentos: uma análise do Acampamento marielle franco - Castro, Juliana Gonçalves (2023)
This work exposes an analysis of the struggle of rural workers for land and political organization in the face of the implementation of large enterprises in Maranhão, having as an empirical reality the Marielle Franco camp. Highlighting the historical expressions of the agrarian question under the aegis of neoliberal politics, which is based on an unequal relationship of territorial and political dispute. Analyzing this problem that is expressed in the dispute between social classes, in an unequal relationship, through the confrontation between rural workers and big capital. Understanding this unfavorable context through organizational expressions of rural workers throughout history, through strategies of struggle and formation of alliances with the Landless Rural Workers Movement - MST, Federation of Rural Workers Agriculturists and Farmers of the State of Maranhão - FETAEMA , Interstate Movement of Babaçu Coconut Breakers – MIQCB, among other organizations. We argue about identity and class consciousness in the construction of this political struggle in opposition to hegemonic power. We conclude that the process of struggle for land is not homogeneous if it is part of a process of emancipation and class consciousness, in which the search for survival of these families leads them to organize and reorganize themselves to face the current perspective